The Trends of Differentiated Instruction Research: Bibliometric Analysis Spanning 1961–2023 - Muhamad Asep Hidayat Amin (Scientia Publica Media, 2024)
In educational research, differentiated instruction, or DI, is a popular subject. Staying up to date with its most recent advancements and frontiers open up new research avenues. This article analyzes developments and trends in differentiated learning using bibliometric analysis between 1961 and 2023. This research focuses on publications from 1961 to 2023, frequently cited keywords, authors who most frequently publish about DI, most frequently cited authors, journals that publish the most, countries that publish the most on DI topics. In the bibliometric analysis, a total of 842 articles were obtained, taken from the Scopus database. The findings indicated that : (1) 2021 marks the pinnacle of publication with 82 papers,(2) Differentiated Instruction, student, teacher, learning, e-learning have been the most popular search terms, (3) Davies et al. (2013), Valli and Buese (2007), Zhu Z (2016), Subban (2006), Reis et al (2011) these have been the papers that have been quoted the most, (4) Katrien Struyven, Marcela Pozas, Letzel, V author with the most number of publication, (5) International Journal of Inclusive Education, Teaching And Teacher Education, ASEE Annual Conference And Exposition Conference Proceedings are among the best journals, (6) Vrije Universiteit Brussel, Universiteit Gent, University of Virginia have been the leading universities, and (7) US, Belgium and Canada have been the leading nations in this sector. This paper is a valuable addition to the subject matter and gives a thorough summary, the scientific environment, and the subject’s future directions.